2007
DOI: 10.1136/jcp.2007.052027
|View full text |Cite
|
Sign up to set email alerts
|

Integration of human papillomavirus type-16 and type-18 is a very early event in cervical carcinogenesis

Abstract: These data imply that integration of HPV-16 and HPV-18 DNA into the host genome occurs in the very early stage of cervical neoplastic progression. These early events may play an initiating role in the malignant transformation of HPV-16- and HPV-18-related low-grade lesions into high-grade dysplasia and invasive carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 28 publications
8
32
0
Order By: Relevance
“…This finding is consistent with recent cross-sectional studies describing the detection of integrated forms of HPV16 and HPV18 in women with low-grade CIN (32)(33)(34). The true incidence of integration events is almost certainly higher than we report because our assay was not designed to identify what are often described as ''mixed infections, '' i.e., those in which E2 continues to be detected because both episomal and integrated forms are present (32)(33)(34), nor could this assay reveal multicopy head-to-tail tandem repeat integrations in which E2 continues to be detected because only the flanking copies are disrupted (26).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with recent cross-sectional studies describing the detection of integrated forms of HPV16 and HPV18 in women with low-grade CIN (32)(33)(34). The true incidence of integration events is almost certainly higher than we report because our assay was not designed to identify what are often described as ''mixed infections, '' i.e., those in which E2 continues to be detected because both episomal and integrated forms are present (32)(33)(34), nor could this assay reveal multicopy head-to-tail tandem repeat integrations in which E2 continues to be detected because only the flanking copies are disrupted (26).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with recent cross-sectional studies describing the detection of integrated forms of HPV16 and HPV18 in women with low-grade CIN (32)(33)(34). The true incidence of integration events is almost certainly higher than we report because our assay was not designed to identify what are often described as ''mixed infections, '' i.e., those in which E2 continues to be detected because both episomal and integrated forms are present (32)(33)(34), nor could this assay reveal multicopy head-to-tail tandem repeat integrations in which E2 continues to be detected because only the flanking copies are disrupted (26). Unlike HPV18-associated cancers and high-grade CIN, in almost all of which an intact E2 gene can no longer be detected, head-to-tail tandem repeats have been reported in HPV16-associated tumors: this pattern of integration might offer a partial explanation for why we found that HPV18 E2 disruption was more common in our cohort (1,8,25,(35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 82%
“…The opinions and data concerning the relationship between the HPV integration and the level of cervical intraepithelial lesions differ according to various authors. Some researchers suggest that integration of HPV is an early event of carcinogenesis [25,26], while others believe that integration is more frequently detected in already existing significant intraepithelial changes [8,9]. However, there is no doubt about the importance of HPV integration and its influence on cervical changes.…”
Section: Discussionmentioning
confidence: 99%
“…As the severity of disease increases, HPV is often found integrated into the host genome, making the interpretation of viral load even more complex. Furthermore, the available viral load data have been generated using different methodologies that may not be directly comparable (13,17,28,29).…”
mentioning
confidence: 99%
“…As the severity of disease increases, HPV is often found integrated into the host genome, making the interpretation of viral load even more complex. Furthermore, the available viral load data have been generated using different methodologies that may not be directly comparable (13,17,28,29).The HPV genome can exist in two physical forms: a closed circular episomal form or linearized and integrated into the host genome. Integration of the viral genome is often associated with the disruption of the E2 gene, which has regulatory control of the oncogenes E6 and E7.…”
mentioning
confidence: 99%